Socially embedded mathematics-related emotions at university: The case of Lumi - Lahdenperä, Juulia; Gildehaus, Lara; Göller, Robin (Finland, 2026)
Emotions have a significant role in learning mathematics. However, research has reported limited evidence on emotions within the university mathematics setting and on the situational nature of emotions. Furthermore, recent studies on university mathematics learning have emphasised the role of “the social” from different theoretical perspectives. Therefore, in the present study, we draw on the social and embedded theory of mathematical affect and consider emotions as socially situated states. With a case-study approach and a reflexive thematic analysis, we provide an explorative illustration of how a mathematics major (here named Lumi) frames their mathematics-related emotions as embedded in the social structures in their university mathematics setting. The findings describe Lumi’s emotions as embedded within the social structure of university mathematics, more temporal social communities, and the artefacts influencing the building of interpersonal relations within these structures. The main finding is that the dynamic changes in emotions involve changes in the social setting. The findings also suggest that there is no need to eradicate negative emotions. Instead, there is a need to develop learning environments with norms and values that support students in communicating and creating various social structures that support their belonging to university mathematics.